Mechanistic Studies on the Bidentate Lewis Acid Catalyzed Domino Inverse Electron-Demand Diels-Alder/Thiol Transfer Reaction - Beeck, Sebastian; Wegner, Hermann A.; Justus Liebig University Giessen (My University, 2023)
Recently, we presented a novel enantioselective multicomponent reaction of phthalazines, aldehydes and thiols accessing thioether-substituted 1,2-dihydronaphthalenes. Herein, a comprehensive investigation on the mechanism of this domino inverse electron-demand (IEDDA)/thiol transfer reaction is disclosed. In particular, the origin of the stereochemical outcome has been rationalized, as well as structural requirement of the thiol component for an efficient transfer step. Detailed NMR spectroscopy studies uncover a competing reaction pathway resulting in N,S-acetals. In addition, DFT computations illuminate the mechanism of the group transfer process and enable an explanation for the formation of the most dominant by-product. The insights allow a direct prediction of suitable substrates for the reaction and provide the basis for further developments of novel stereoselective domino reactions.
Keywords: ddc:540